عزل وتشخيص الفطريات المسببة لذبول بادرات نبات البلنكو Lallemanti royleana - شاكر كونر عبد الوهاب (Al-Nahrain Journal of Science, 2018)
This study included isolation and diagnosis of the fungi cause damping–off Balangu seedlings Lallemantia royleana (Benth. in Walla.) in nurseries belonging to the division of medicinal plants and herbal spices for Industrial Crops/ Ministry of Agriculture. The results showed that fungi Rhizoctonia solani Kühn and Fusarium solani (Mart.) Sacc., were the causative agent of seed rot and seedling damping-off on Balangu plants (44.4, 22.2%), respectively. Pathogenicity study of each Fungus R. solani and F. solani showed a seed rot in apercentage of (60, 16%) and seedling damping off (24,35.3%), respectively,. Trichoderma harzianum appeared efficient antagonist against both pathogens R. solani and F. solani at rate (2 and 1.6), respectively.